2019
DOI: 10.1111/zph.12609
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time quantitative PCR‐based detection of Coxiella burnetii in unpasteurized cow's milk sold for human consumption

Abstract: Coxiella burnetii is a zoonotic pathogen with a worldwide distribution that is responsible for Q fever in humans. It is a highly infectious bacterium that can be transmitted from cattle to humans through the consumption of unpasteurized milk. We report the molecular identification of C. burnetii in raw cow's milk being sold directly for human consumption in Brazil without official inspection or pasteurization. One hundred and twelve samples of raw milk were analysed by real‐time quantitative PCR (qPCR), and C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…Nevertheless, recent multi spacer typing (MST) and multi-locus variable tandem repeat analysis (MLVA) investigations in Brazil have identified evidence of unique genotypes [ 17 ], and this emphasizes the need of epidemiological and virulence studies that aim to better understand the disease in this region. MST-74, detected in Brazil, belongs to the same phylogenetic branch as MST 20 and MST 61 [ 16 ], which places the strains circulating in Brazil in genomic group III of Hendrix et al [ 70 72 ]. In a recent virulence study, it was shown that strains belonging to genomic groups I and III were more virulent, with increased pathogenic potential compared to C .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, recent multi spacer typing (MST) and multi-locus variable tandem repeat analysis (MLVA) investigations in Brazil have identified evidence of unique genotypes [ 17 ], and this emphasizes the need of epidemiological and virulence studies that aim to better understand the disease in this region. MST-74, detected in Brazil, belongs to the same phylogenetic branch as MST 20 and MST 61 [ 16 ], which places the strains circulating in Brazil in genomic group III of Hendrix et al [ 70 72 ]. In a recent virulence study, it was shown that strains belonging to genomic groups I and III were more virulent, with increased pathogenic potential compared to C .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the possibility of transmission through consumption of cattle milk and dairy products should not be neglected, as the presence of C . burnetii has been evaluated in such products in Brazil [ 16 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed qPCR, targeting the IS1111 element with specific primers and probes developed by ANSES (Sophia Antipolis, France) and produced by GENEWIZ (Leipzig, Germany). The quantitative PCR reaction was performed in a total volume of 25 µL, as described by Mioni et al [7]. A standard curve ranging from 2 × 10 2 to 2 × 10 7 genome equivalent (GE) bacteria/mL was used for quantification proposes.…”
Section: Quantitative Pcr (Qpcr)mentioning
confidence: 99%
“…The importance of Q fever, in terms of public health, increased after the outbreak in the Netherlands, where more than 4000 people became ill and 50,000 animals were slaughtered to control the epidemics [5,6]. Recently, we reported the presence of bacteria in Brazil by qPCR in raw Pathogens 2020, 9,30 2 of 11 cow's milk sold directly for human consumption and its risk to human health [7]. The use of molecular typing is useful to determine the source of the outbreak, leading to more precise preventive measures [8].…”
Section: Introductionmentioning
confidence: 99%